Outcome and determinants of Directly Observed Short-course treatment for tuberculosis patients - Al-Janabi , Alaa Hussein Khudhair (South Asian Journal of Social Sciences and Humanities, 2023)
Background: The Directly Observed Treatment Short Course (DOTS) is a well-established and cost-effective strategy for treating Tuberculosis. It efficiently transforms infectious cases into non infectious ones, effectively interrupting the transmission cycle of the disease. Objectives: Measure the treatment outcomes in TB patients during 2016-2020, describe the socio-demographic and clinical profile of TB patients and evaluate the performance of the National TB program in Babil governorate based on WHO indicators. Methods: A descriptive cross-sectional study was done. All TB patients in the NTP Center of Babil governorate under the DOTS program from 2016 to 2020 were included. A form was developed to compile socio-demographic data, clinical presentation, and treatment outcomes. Results: A total number of cases was 1723. The mean age was 40.0 (± 21.0) years. The female constituted 53.8% of cases. The patients aged ≥ 65 years had the highest percentage of total cases 279 (16.2%). Pulmonary tuberculosis (PTB) constituted 56.1% of the cases 50.5% of them had smear-positive. The most common site for extrapulmonary tuberculosis (EPTB) was lymph nodes 41.1%. Treatment success was attained in 93.7%, while 3.3% of patients dead. The patients aged ≥ 65 years have the lowest success rate and highest treatment unsuccess rate opposite to young age groups (p 0.002). Conclusion: The treatment outcome target planned by WHO was achieved. The case detection rate of all form was low. The age and the site of TB significantly affected the outcome of treatment.